PERANAN POHON PELINDUNG DALAM MENENTUKAN PRODUKTIVITAS KOPI - Evizal, Rusdi; Tohari, Tohari; Prijambada, Irfan Dwija; Widada, Jaka (JURNAL AGROTROPIKA, 2020)
Shade trees of legume in par-ticular have ecological function such as litter fall production, N fixation, nutrient acquisition from deep soil, and shade provision. Shade trees may influence coffee bean yield both increasing and decreasing the yield. To evaluate the role of shade trees in determining coffee yield, the experimental plots were constructed at benchmark site of Conservation and Sustainable Management of Below-Ground Biodiversity (CSM-BGBD), in Sumberjaya Subdistrict, West Lampung, Indonesia. Shade trees of Coffea canephora agro-ecosystems to be examined were Gliricidae sepium, Erythrina sububrams, Michelia champaca, and no shade. The results showed that agro-ecosystem shaded with Gliricidae sepium, Erythrina sububrams, Michelia champaca gave positive return of N, P, K. Total N from litter fall of shade trees and level of shading had quadratic regression with coffee yield. Shading on July significantly determined coffee yield with negative coefficient. Key words: shade tree, coffee yield, litter fall, level of shading